BOOK REVIEWS (Journal of Finance, 1974)
Book reviewed in this article: The Banking Crisis of 1933 . By S usan E stabrook K ennedy Studies in The Theory of Capital Markets , Edited by M ichael C. J ensen Bank‐Administered Commingled Pension Funds . By E dward M alca . Introduction to Investments and Finance: Theory and Analysis , by F red B. R enwick . Conglomerates Unlimited: The Failure of Regulation . By J ohn F. W inslow . European Monetary Unification . By G iovanni M agnifico . International Trade and Investment by Franklin R. Root Managing the Dollar . By S herman J. M aisel . Theory of Demand: Real and Monetary . By M. M orishima and others. Public Finance . By B ruce R. D avie and B ruce F. D uncombe .